The novel high-affinity humanized antibody IMM40H targets CD70, eliminates tumors via Fc-mediated effector functions, and interrupts CD70/CD27 signaling - Li, Song; Chen, Dianze; Guo, Huiqin; Liu, Dandan; Yang, Chunmei; Zhang, Ruliang; Wang, Tianxiang; Zhang, Fan; Bai, Xing; Yang, Yanan; Sun, Nana; Zhang, Wei; et al. (Frontiers in Oncology, 2023)
Background: A significant level of CD70 can be detected in various types of tumor tissues and CD27 is expressed on Treg cells, but CD70 expression is low in normal tissues. The interaction between CD70 and CD27 can stimulate the proliferation and survival of cancer cells and increase the level of soluble CD27, which is associated with poor prognosis in patients with lymphoma and certain solid tumors. Thus, it is a promising therapeutic target for the treatment of many major CD70+ cancer indications, including CD70+ lymphoma, RCC, NSCLC, HNSCC and OC. Methods: IMM40H was obtained through hybridoma screening and antibody humanization techniques. IMM40H was evaluated for its binding, blocking, Fc-dependent effector functions and antitumor activity characteristics in various in vitro and in vivo systems. The safety and tolerability profile of IMM40H were evaluated through single and repeated administration in cynomolgus monkeys. Results: In vitro cell-based assays demonstrated that IMM40H had considerably stronger CD70-binding affinity than competitor anti-CD70 antibodies, including cusatuzumab, which enabled it to block the interaction of between CD70 and CD27 more effectively. IMM40H also exhibited potent Fc-dependent effector functions (ADCC/CDC/ADCP), and could make a strong immune attack on tumor cells and enhance therapeutic efficacy. Preclinical findings showed that IMM40H had potent antitumor activity in multiple myeloma U266B1 xenograft model, and could eradicate subcutaneously established tumors at a low dose of 0.3 mg/kg. IMM40H (0.3 mg/kg) showed therapeutic effects faster than cusatuzumab (1 mg/kg). A strong synergistic effect between IMM01 (SIRPα-Fc fusion protein) and IMM40H was recorded in Burkitt’s lymphoma Raji and renal carcinoma cell A498 tumor models. In cynomolgus monkeys, the highest non-severely toxic dose (HNSTD) for repeat-dose toxicity was up to 30 mg/kg, while the maximum tolerated dose (MTD) for single-dose toxicity was up to 100 mg/kg, confirming that IMM40H had a good safety and tolerability profile. Conclusion: IMM40H is a high-affinity humanized IgG1 specifically targeting the CD70 monoclonal antibody with enhanced Fc-dependent activities. IMM40H has a dual mechanism of action: inducing cytotoxicity against CD70+ tumor cells via various effector functions (ADCC, ADCP and CDC) and obstructs the proliferation and activation of Tregs by inhibiting CD70/CD27 signaling.